Сoordination of supply and demand alternative energy in Russia industrial with organizational solution - G. N. Ryazanova (Управление)
One of the key factors affecting the competitiveness of an enterprise is low energy costs. Despite the status of Russia as an energy superpower, Russian companies are paying a high price for electricity. It has increased the past 10 years more than 3 times. In addition the traditional energy sources, there are renewable energy sources, which include solar, geothermal, bioenergy, and others. They are close in certain cases and are able to give energy. In developed countries, the production and consumption of energy from renewable sources for industry is growing every year. In Russia it is used hardly, but the potential of renewable energy is huge. This is due to the peculiarities of the country – there are a lot of hydrocarbons in Russia, and industry has focus on hydrocarbon energy sources. At the same time, in our country there are the situations where renewables can be an essential complement centralized system of electrification. But in Russia there is no mechanism of regulation of the supply / demand of alternative energy. There are not institutional conditions for state regulation of renewable energy production, there is not renewables market. The paper proposes an organizational solution that solves the problem of the coordination of the supply / demand in the Russian context.